CoP nanosheet assembly grown on carbon cloth: A highly efficient electrocatalyst for hydrogen generation. (July 2015) - Yang, Xiulin; Lu, Ang-Yu; Zhu, Yihan; Hedhili, Mohamed Nejib; Min, Shixiong; Huang, Kuo-Wei; Han, Yu; Li, Lain-Jong
Abstract: There exists a strong demand to replace expensive noble metal catalysts with cheap metal sulfides or phosphides for hydrogen evolution reaction (HER). Recently metal phosphides such as Nix P, FeP and CoP have been considered as promising candidates to replace Pt cathodes. Here we report that the nanocrystalline CoP nanosheet assembly on carbon cloth can be formed by a two-step process: electrochemical deposition of Co species followed by gas phase phosphidation. The CoP catalyst in this report exhibits a Tafel slope of 30.1 mV/dec in 0.5 M H2 SO4 and 42.6 mV/dec in 1 M KOH. The high HER performance of our CoP catalysts is attributed to the rugae-like morphology which results in a high double-layer capacitance and high density of active sites, estimated as 7.77×10 17  sites/cm 2 . Graphical abstract: Nanocrystalline CoP nanosheet assembly on carbon cloth formed by electrochemical deposition of Co species followed by gas phase phosphidation is an efficient cathode for water electrolysis. Highlights: Nanocrystalline CoP is obtained by gas phosphidation of electroplated Co species. The CoP catalyst exhibits a Tafel slope (30.1 mV/dec) comparable to Pt in acids. The CoP catalyst shows a Tafel slope of 42.6 mV/dec in basic solutions. The high HER activity is owing to its large surface area and active site density.